Responsiveness of the Berg Balance Scale in patients early after stroke. (18th May 2016) - Saso, Adam; Moe-Nilssen, Rolf; Gunnes, Mari; Askim, Torunn
ABSTRACT: The Berg Balance Scale (BBS) has previously shown good measurement properties. However, its ability to detect important change in patients early after stroke is still unknown. The purpose of the present study was to determine the minimal important change (MIC) and its relation to the minimal detectable change (MDC) for BBS in patients early after stroke. This prospective follow-up study included patients within the first 2 weeks after onset of stroke. The BBS, Barthel Index, and Scandinavian Stroke Scale were obtained at inclusion and 1 month later. At the follow-up assessment, the Patient Global Impression of Change was obtained. A receiver operating characteristic (ROC) curve was used to calculate the cut-off value for the MIC. Fifty-two patients (mean age of 78.7, SD 8.5 years) were included. All measures showed a significant improvement from baseline to follow-up. The ROC analysis identified a MIC of ≥6 BBS points, while the MDC was 5.97 BBS points at the 80% confidence level. This study shows that a change of 6 BBS point or more can be considered an important change for patients in the sub-acute phase after stroke, which also represents an 80% probability of exceeding the measurement error. A total of 80% of unchanged patients would display random fluctuations within the bounds of MDC80, while 20% of unchanged patients would exceed MDC80.